Criminal liability for tax evasion: current realities - Marushchak , Oleksandr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
This article deals with the criminal law characteristics of the criminal offense under Article 212 of the Criminal Code of Ukraine. The author emphasizes that the state tax policy is focused on the introduction, legal regulation and organization of the process of collection of taxes and payments to centralized funds. It is emphasized that not all actions of economic entities aimed at reducing tax pressure contradict the law: there are legal ways to minimize tax liabilities. The author examines the concepts of »tax evasion” and “tax avoidance” and analyzes the main schemes that can be implemented both in violation of the law (tax fraud) and within the framework of legislation (use of legislative gaps, contradictions or exceptions). The author analyzes the legislative provisions of Ukraine, in particular, the Code of Ukraine on Administrative Offenses, the Criminal Code of Ukraine and the Tax Code of Ukraine, which regulate liability for tax evasion, duties and mandatory payments.The author focuses on the methods of tax evasion which are not specified in Article 212 of the Criminal Code of Ukraine, which gives pre-trial investigation authorities flexibility in responding to new challenges arising in the course of development of tax evasion schemes.Based on the analysis of the court practice of criminal proceedings in this category, the author notes the complexity of the construction of Article 212 of the Criminal Code of Ukraine, and the difficulty in proving the intent of persons held criminally liable, which results not only in certain shortcomings during the pre-trial investigation, but also in the acquittals by the courts.  The author comes to the conclusion that individuals and legal entities are obliged to pay taxes and fees in the manner and amounts established by law, and the state must ensure both proper control over the fulfillment of this obligation and prosecution of perpetrators in the manner and within the limits established by law.